DataverseNO: A National, Generalist Repository for Data from the Long Tail of Research - Conzett, Philipp; Leif, Longva; Nilsen, Karl Magnus (Septentrio Conference Series, 2022)
DataverseNO (https://dataverse.no/) is a national, generic repository for open research data, owned and operated by UiT The Arctic University of Norway. The technical infrastructure of the repository is based on Dataverse, a community-driven open-source application, which is developed by an international developer and user community led by Harvard University. DataverseNO supports the FAIR Guiding Principles for scientific data management and stewardship, and is CoreTrustSeal certified (Conzett 2020). DataverseNO is based on collaboration between Norwegian research organizations. Datasets from partner institutions are published in institutional collections. Currently, 14 research organizations are partnering with DataverseNO. UiT is responsible for training and support for institutional collection managers, whereas the partner institutions are responsible for the curation of their institutional data and local user support. To ensure that data deposited into DataverseNO comply with the DataverseNO policies and guidelines they are curated by qualified research data service staff before they are published. The DataverseNO curators join forces in the DataverseNO curation network. Datasets in DataverseNO are equipped with persistent identifiers (DOIs, Digital Object Identifiers) at dataset and file level. DOIs serve as unique references to datasets and files and make them searchable in discovery services like B2FIND – EUDAT, Bielefeld Academic Search Engine (BASE), DataCite Search, Google Dataset Search, and Oria/Primo. On December 1, the last day of this year’s Munin Conference, DataverseNO will be turning 5 years!